Sustainable solid waste management in tourism villages: Challenges and strategies for environmental sustainability tourism village - Putridira, Nursyahbani; Ramdhani, Meilia Dwi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Solid waste management plays a crucial role in ensuring sustainable tourism development. In Guwosari Tourism Village, the introduction of the integrated waste processing site (TPS 3R) Go Sari, initiated by Badan Usaha Milik Desa (BUM Desa) Guwosari Maju Sejahtera in 2019, has expanded its service area, aiming to cover 550 families by 2024. Despite its success, there are challenges related to the effectiveness of the waste management system in the village, particularly concerning waste incineration processes and the overall sustainability of the program. Methods: This study uses a literature review approach, collecting relevant data based on keywords such as Environmental Sustainability, Go-Sari, Guwosari Tourism Village, Incinerator, Municipal Solid Waste, and Waste Management Strategy. The qualitative descriptive data evaluation method allows for a thorough analysis of the existing solid waste management system at TPS 3R Go-Sari. Findings: The study identifies several issues in the solid waste management system at TPS 3R Go-Sari, including air pollution caused by smoke from incinerators during the burning of waste residues. Additionally, the accumulation of ash from incineration poses environmental concerns. Moreover, only about 20% of the village's total waste is processed at the facility, and the high cost of waste collection is a burden for the villagers. Conclusion: While TPS 3R Go-Sari has made strides in managing solid waste in Guwosari Tourism Village, it faces significant challenges such as air pollution, limited waste processing capacity, and high collection costs. The implementation of the Zero Waste concept shows potential but requires addressing these issues for better sustainability and community impact. Novelty/Originality of the Study: This study provides a unique examination of the practical challenges of applying the Zero Waste concept in a tourism village setting, focusing on the environmental and financial issues surrounding waste incineration and management. It also offers insights into the integration of sustainable waste practices in rural tourism areas.